Quality attributes of ready-to-eat bison meat snacks during 40°C accelerated storage - Heitschmidt, James Daniel (Kansas State University, 2015)
The market for bison meat products is increasing as a result of consumer interest in meat from animals that are primarily grass fed. Quality attributes of a bison meat snack containing cranberry and apple pieces and formed into a bar or bite were evaluated during 18 weeks of storage in a 40°C accelerated shelf life cabinet to simulate an ambient shelf life of 18 months. The products were formulated at a commercial facility; bars were packaged into a vacuum package, while bites were packaged in a sealed bag with an oxygen absorber. External color, pH, sensory attributes, Warner-Bratzler shear force (WBSF), water activity (a[subscript]w), and yeast and mold populations were determined. External color, pH, and a[subscript]w were evaluated on weeks 0, 3, 5, 12, 14, and 18 of accelerated storage. Sensory attributes, WBSF shear force, and yeast and mold populations were evaluated on weeks 0, 3, 5, 12, and 18. At week 0 and week 18, external L* for the bars and bites were similar (P>0.05); however, trained panelists observed both products becoming visually darker (P<0.05) by weeks 3 and 12 for bars and bites, respectively. For bars and bites, a* values remained constant (P>0.05) through week 5 and 12, respectively, and then became less red (P<0.05) by week 14 for bars and bites. Bars continued to become less red (P<0.05) by week 18. Bar a[subscript]w remained constant (P>0.05) from week 0 through week 18, while bites a[subscript]w remained constant through week 5, and then declined (P<0.05) to a mean a[subscript]w of 0.83 by week 18. Bar pH remained constant (P>0.05) through week 5, and then declined (P<0.05) to 4.32 at week 18. Bites pH declined (P<0.05) from 4.63 at week 0 to 4.22 at week 18. Yeast and mold populations were non-detectable throughout storage for both products. Panelists found that bar bite and tenderness remained similar (P>0.05) from 4.63 at week 0 through week 18. Bites became softer and more tender (P<0.05) from week 0 to week 3, and then remained similar (P>0.05) through week 18. Bars and bites WBSF remained similar (P>0.05) from week 0 through week 18. Bar sweetness and fruit flavor intensity declined (P<0.05) and bar and bite off-flavors increased (P<0.05) by the end of storage. Changing product size from bars to bites and using a vacuum bag versus a sealed bag with an oxygen absorber influenced product characteristics during accelerated storage. The recommended shelf life for bars and bites would be equivalent to 5 months at ambient temperature based on 5 weeks at accelerated storage at 40°C.
Keywords: Accelerated Storage Bison; Food Science (0359)